Assessment of poor functional status and its predictors among the elderly in a rural area of West Bengal - Jayeeta Burman; Sembagamuthu Sembiah; Aparajita Dasgupta; Bobby Paul; Neeraj Pawar; Adrija Roy (Wolters Kluwer Medknow Publications, 2019)
Context: Functional ability considered a proxy for healthy aging, not only related to mental and physical health but it also determines social well-being. Eliciting the determinants of functionality components among the elderly will assist in evolving with appropriate plans at both domiciliary and facility level to eliminate their sufferings and disabilities. Aim: The aim of this study is to find out the magnitude of poor functional status among the elderly and its predictors. Materials and Methods: This is a community-based cross-sectional study conducted among 246 geriatric people in a rural area of West Bengal from August 2017 to December 2017; data were analyzed using the SPSS software (version 16.0. Chicago, SPSS Inc.). Logistic regression analysis was performed to find out the factors associated with poor functional status (activities of daily living [ADL] and instrumental ADL [IADL]). Results: The study concluded that 32.4% and 59.3% were dependent for basic ADL and IADL, respectively. Binary logistics showed people aged >70 years, female gender, less than primary level education, widowed/separated, who lived in the joint family, poorest percentile of economic status, who were depressed and who suffered from multimorbidity had increased odds of dependency for ADL and IADL. In multivariate logit regression, age> 70 years and depression remained significant for ADL; in addition, marital status, education, and family type remained significant for IADL. Conclusion: There should be a provision for community-based comprehensive geriatric health and disability assessment, as it enables older people to avert the illness at the early stage, to delay the onset of disabling diseases. This will ensure their participation in the upliftment of the society, and they thus will be less dependent on their progeny.